Improvement Strategy for Procurement Using the Hanlon Method at the Public Health Centers in Kediri - Prasetyawan, Fendy; Widodo, Gunawan Pamudji; Purwidyaningrum, Ika (PT FORMOSA CENDEKIA GLOBAL, 2023)
Public Health Center (PHC) was a health center that needed and demanded by the community, accordingly availability and quality of medicines at PHC should met the needs. Purpose of this study were to determine the level of conformity and specify selection and procurement strategies for pharmaceutical service standards in Kediri's PHC based on priority scale of problem using Hanlon analysis. Design of this study was a non-experimental study, with data were analyzed quantitative and qualitative, collected using questionnaire instrument by conducting interviews, while results of this study was data in the form of counting results from respondent’s answers. The research results indicate that the procurement compliance level at the Public Health Centers in Kediri City has one problematic indicator, namely the percentage of procurement compliance with the actual usage for each drug item. Meanwhile, three indicators that are in compliance include the frequency of procurement for each drug item, the frequency of invoice errors, and the frequency of delayed payments by Puskesmas in relation to the established timelines.